2018
DOI: 10.1038/s41598-018-29245-5
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of biomass degradation by alternative σ factors in cellulolytic clostridia

Abstract: Bacteria can adjust their genetic programs via alternative σ factors to face new environmental pressures. Here, we analyzed a unique set of paralogous alternative σ factors, termed σIs, which fine-tune the regulation of one of the most intricate cellulolytic systems in nature, the bacterial cellulosome, that is involved in degradation of environmental polysaccharides. We combined bioinformatics with experiments to decipher the regulatory networks of five σIs in Clostridium thermocellum, the epitome of cellulol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 52 publications
3
33
0
Order By: Relevance
“…Previous work indicated that C. thermocellum σ I3 and σ I11 from B. cellulosolvens use highly conserved promoter sequences to regulate genes encoding pectin‐degrading enzymes …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous work indicated that C. thermocellum σ I3 and σ I11 from B. cellulosolvens use highly conserved promoter sequences to regulate genes encoding pectin‐degrading enzymes …”
Section: Resultsmentioning
confidence: 99%
“…In order to identify the conserved promoter motif for genes encoding xylan‐degrading enzymes, we performed bioinformatics analysis to identify the putative regulon of C. clariflavum σ I4 . We first compared the promoter regions of C. clariflavum sigI4 and A. cellulolyticus sigI4 to the previously predicted σ I ‐dependent promoter of B. cellulosolvens sigI1 . As shown in Figure A, the predicted −35 region of the putative σ I promoter of C. clariflavum sigI4 has a conserved AAAA tetrad, and a conserved CGA triad three nucleotides upstream of the latter tetrad.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Activation of ECF factors therefore depends on release from the constraint inflicted by anti-factors. This method of factor activation has been well documented in another cellulolytic bacterium, C. thermocellum, in which a set of unique alternative and anti-factors with extracellular polysaccharide-sensing modules regulate the composition of the cellulosome in response to the presence of extracellular polysaccharides (30,31,36,37).…”
Section: Discussionmentioning
confidence: 99%